Innovation in the Professional Formation and Development of Future Teachers - Tsiuniak , Oksana; Yaremchuk , Nataliya; Haliuka , Olha; Prots , Marta (Insight: the psychological dimensions of society, 2024)
The aim of the empirical research is to find out and substantiate the psychological content parameters of innovation in the professional formation and development of future teachers. The tasks are: determination of correlations of parameters of higher education students’ professional readiness for innovative activities with independent variables; finding statistically significant differences between the respondents in the samples of bachelors (group I) and master’s students (group II); comparison of the researched groups with high and low levels of the formation of the coefficients of innovation. Methods: retrospective analysis, generalization, systematization and comparison; the author’s questionnaire “Professional readiness of students for innovative activities” (RIA) (Tsiuniak, 2021); method “Diagnostics of the motivational structure of the personality” (DMSP) (Milman, 1990); method “Teacher’s abilities for creative self-development” (TACSd) (Nikishina, 2009). Results. It was found that there are no statistically significant differences in the determined parameters between the samples of bachelors (group I) and master’s students (group II). A positive tendency was stated in group I in the quantitative coefficient of innovation QCI (М=.68; SD=.22; Me=.68) and in group II – the qualitative coefficient of innovation Q2CI (М=.62; SD=.23; Me=. 61). It was established that the coefficients of innovation have four statistically significant correlations with independent variables: creative activity, social usefulness, active self-development, stopped self-development (р
Keywords: educational process, professional training, professional readiness, primary school teacher, university, distance learning, digital educational environment.